Recall and response of smokers and recent quitters to the Australian National Tobacco Campaign. (23rd July 2003) - Wakefield, M; Freeman, J; Donovan, R
Abstract : Objective: To track national population indices of recall and response among smokers and recent quitters to an ongoing national televised anti-smoking campaign in Australia. Method: National cross sectional population telephone surveys of adults. Main outcome measures: Unprompted recall of advertising; recognition of advertising; campaign attributed encouragement to quit or stay quit; unprompted awareness of smoking related health effects; new learning about smoking and health; and agreement with campaign related attitudes. Results: Campaign advertising continued to be highly memorable over the period of study, with 88% having confirmed recognition in 2000. Campaign advertising was consistently thought by half of smokers who had seen it to make them more likely to quit (49% in 2000). Specific changes between surveys in unprompted awareness of smoking related health effects, new learning about smoking and health, and agreement with campaign related attitudes were observed in relation to the main messages of the advertisements, which were time sensitive according to the year of launch of the advert. The "artery" advertisement was associated with the largest and most consistent positive change in all of these parameters. The proportion of respondents who disagreed that the dangers of smoking had been exaggerated increased significantly from 59% in May 1997 to 68% in November 2000. Conclusion: A national campaign using graphic advertising to emphasise the health risks of smoking can make significant population wide contributions to improving new learning about smoking damage and positively influence attitudes about smoking risks.